Distribution of quetiapine and metabolites in biological fluids and tissues. (February 2020) - Vignali, Claudia; Freni, Francesca; Magnani, Camilla; Moretti, Matteo; Siodambro, Chiara; Groppi, Angelo; Osculati, Antonio Marco Maria; Morini, Luca
Highlights: Quetiapine and main metabolties distribution in post-mortem cases. The quetiapine/metabolites ratio was measured in different matrices. Postmortem redistribution of quetiapine might influence data reliability. The metabolites are less affected by post-mortem redistribution. Abstract: Quetiapine is an atypical antipsychotic drug, frequently found in post-mortem samples. The quantitative determination of active metabolites may help in the interpretation of the potential toxic effects of the parent drug and its role in death. A fully validated LC–MS/MS method was developed for the identification and quantification of quetiapine and two main metabolites (N-desalkylquetiapine and 7-hydroxyquetiapine) in blood, biological fluids and tissues. Then, the distribution of analytes in different matrices was evaluated. LODs of 0.9, 0.3 and 0.3 ng/mL were calculated for quetiapine, N-desalkylquetiapine and 7-hydroxyquetiapine respectively; while a LOQ at the concentration of 10.0 ng/mL was defined for the three analytes. 13 post-mortem positive real cases have been included in the experiment. The results revealed that quetiapine and N-desalkylquetiapine might undergo a significant post-mortem redistribution, while 7-hydroxyquetiapine is less affected by this factor. N-desalkylquetiapine could be found in blood in relatively high concentrations in comparison to those of quetiapine; therefore, it should be always advisable to measure both the analytes. The analysis of tissues could provide additional data on potential intoxication with quetiapine.